Henry Darnall indenture - Darnall, Henry
Indenture (1728 April 3) relating to the transfer to John Hyde by Henry and Ann Digges Darnall of 6700 acres of His Lordship's Kindness, their estate in Prince George's County, Md.
Planter, of Prince George's County, Md. Died 1737.
Collection material in English.
Keywords: Darnall, Ann Digges; Hyde, John, -- 1655-1732.; Deeds -- Maryland -- Prince George's County; Land tenure -- Maryland -- Prince George's County; Land titles -- Maryland -- Prince George's County; His Lordship's Kindness (Md. : Estate); Prince George's County (Md.) -- History